Students’ Satisfaction and Learning Motivation toward Online Learning during the Covid-19 Pandemic - Farida Mayar; Febri Wandha Putra; M. Aries Taufiq; Fenny Ayu Monia; Siti Osa Kosassy (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aimed to examine students’ learning motivation and satisfaction in attending lectures during the Covid-19 pandemic. This descriptive correlational study involved 155 students majoring in Early Childhood Education Teacher Education (PG-PAUD) registered in 2019, who were selected through total sampling technique. Data in this study were obtained by distributing two types of questionnaires (learning satisfaction level questionnaire and learning motivation questionnaire) to all students. Before distributing the questionnaires, they were validated by product moment correlation; then, their reliability was tested through Alpha Cronbach. Then, the data were analyzed descriptively and were examined by simple regression. This study revealed that the level of student satisfaction in attending lectures during the Covid-19 pandemic was at the medium category (48.38%) and their learning motivation was also at medium category (55.48%). Therefore, this study concluded that students were dissatisfied with the learning process conducted by the lecturer during the Covid-19 pandemic. As a consequence, this low level of learning satisfaction decreased the students’ motivation to attend the lecturers during the Covid-19 Pandemic.